Understanding State Rulemaking Processes: Developing Fracking Rules in Colorado, New York, and Ohio1. Issue 2 (March 2014) - Rinfret, Sara; Cook, Jeffrey J.; Pautz, Michelle C.
Abstract Rulemaking is an integral component of environmental policy at both the federal and state level; however, rulemaking at the state level is understudied. With this research, we begin to fill that gap by focusing on rulemaking regarding the issue of hydraulic fracturing (fracking) in three states: Colorado, New York, and Ohio. This policy issue is well suited to begin exploring state‐level rulemaking processes because the federal government has left fracking regulation to the states. Through semistructured interviews with a range of actors in the rulemaking process across these states, we establish a foundation from which future research in this area may build. This exploratory research yields some valuable insights into the roles different stakeholders are playing in regulating fracking in these three states, and our findings may be useful for explaining state‐level rulemaking more generally.